Heaven's Interpreters : Women Writers and Religious Agency in Nineteenth-Century America - Reed, Ashley, 1975- (Book collections on Project MUSE., 2020)
"Heaven's Interpreters demonstrates how women writers of the American antebellum period used popular fictional genres to engage in theological debates and, in the process, brought into being new models of religious agency"--